KEPEMIMPINAN GEMBALA BAGI KETUA PROGRAM STUDI PENDIDIKAN DALAM MEMIMPIN PARA DOSEN DI TEACHERS COLLEGE - Wiputra Cendana (Jurnal Theologia Forum STFT Surya Nusantara, 2019)
The shepherding leadership model that Jesus did in the world has posed a perfect model for the leaders who are willing to do the shepherding leadership. The higher education or organization faces a challenge to implement the shepherding leadership. An intentional personal relationship with Jesus Christ becomes the initial foundation to comprehend the shepherding leadership that will be implemented later on. This research is aimed to know The Shepherding Leadership Towards Study Program Chair in Leading the Lecturers in Teachers College. The Shepherding Leadership is one of the roles of a study program chair at the Faculty of Education Teachers College. This research is a phenomenology qualitative research with in-depth interview and semi-structured interview as the techniques for gathering the data. The data validation will be examined using validation from the lecturers as the interviewees. The result of the research shows that the study program chair as the shepherd has taken their roles in completing each of their works well, while the duty as a shepherd needs to be done in a focus and intention always.